The Potential Role of Nrf2 Signaling in Leishmania Infection Outcomes - Vivarini, Aislan de Carvalho; Lopes, Ulisses Gazos (Frontiers in Cellular and Infection Microbiology, 2020)
Nrf2 [nuclear factor erythroid 2-related factor 2 (Nrf2)] regulates the expression of a plethora of genes involved in the response to oxidative stress due to inflammation, aging, and tissue damage, among other pathological conditions. Deregulation of this cytoprotective system may also interfere with innate and adaptive immune responses. Oxidative burst, one of the main microbicidal mechanisms, could be impaired during initial phagocytosis of parasites, which could lead to the successful establishment of infection and promote susceptibility to diseases. A wide diversity of infections, mainly those caused by intracellular pathogens such as viruses, bacteria, and protozoan parasites, modulate the activation of Nrf2 by interfering with posttranslational modifications, interactions between different protein complexes and the immune response. Nrf2 may be induced by pathogens via distinct pathways such as those involving the engagement of Toll-like receptors, the activation of PI3K/Akt and endoplasmic reticulum stress. Recent studies have revealed the importance of Nrf2 on leishmaniasis. This mini-review discusses relevant findings that reveal the connection between Leishmania-induced modifications of the host pathways and their relevance to the modulation of the Nrf2-dependent antioxidative response to the infection.